Math, asked by rehadewan08, 4 months ago

if x = 2 + √3 , find the value of ( x² + 1 / x² )^2


( don't give unnecessary answers ) ( give correct answer only )​

Attachments:

Answers

Answered by Athul4152
1

x = 2 + √3

x² = ( 2 + √3)²

= 2²+ 4√3 + 3

= 4 + 4√3 + 3

= 7 + 4√3

(x² + 1/x²)² = (7 +4√3 +( 1 / (7+4√3)))²

= (7+4√3)² + (2 .7+4√3.1/7+4√3) +( 1/7+4√3)²

= 7²+(4√3)²+56√3 + 2 + [1/(7²+8√3 +( 4√3)²]

= 49 + 48 + 56√3 + 2 + [1/( 97 + 56√3)]

= 97+56√3 +( 1 / (97 +56✓3) )+ 2

on substituting the values of √3, we get the answer 196

Answered by mathdude500
3

\large\underline{\sf{Given- }}

 \red{\rm :\longmapsto\:x = 2 +  \sqrt{3}}

\large\underline{\sf{To\:Find - }}

 \red{\rm :\longmapsto\: {\bigg( {x}^{2} + \dfrac{1}{ {x}^{2} }  \bigg) }^{2}}

Solution :-

Given that

{\rm :\longmapsto\:x = 2 +  \sqrt{3}}

So,

\rm :\longmapsto\:\dfrac{1}{x}

\rm \:  =  \:  \: \dfrac{1}{2 +  \sqrt{3} }

☆ On rationalizing the denominator, we get

\rm \:  =  \:  \: \dfrac{1}{2 +  \sqrt{3} }  \times \dfrac{2 -  \sqrt{3} }{2 -  \sqrt{3} }

\rm \:  =  \:  \: \dfrac{2 -  \sqrt{3} }{ {(2)}^{2}  -  {( \sqrt{3})}^{2} }

\rm \:  =  \:  \: \dfrac{2 -  \sqrt{3} }{4 - 3}

\rm \:  =  \:  \: \dfrac{2 -  \sqrt{3} }{1}

\rm \:  =  \:  \: 2 -  \sqrt{3}

\bf\implies \:\dfrac{1}{x} = 2 -  \sqrt{3}

Consider,

\bf :\longmapsto\: {x}^{2}  + \dfrac{1}{ {x}^{2} }

\rm \:  =  \:  \:  {\bigg(x + \dfrac{1}{x}  \bigg) }^{2}  - 2 \times x \times \dfrac{1}{x}

\red{\bigg \{ \because \: {x}^{2} +  {y}^{2} =  {(x + y)}^{2} - 2xy\bigg \}}

\rm \:  =  \:  \:  {\bigg(x + \dfrac{1}{x}  \bigg) }^{2}  - 2

[☆ On substituting the values, we get]

\rm \:  =  \:  \:  {\bigg(2 +  \sqrt{3}  + 2 -  \sqrt{3}  \bigg) }^{2}  - 2

\rm \:  =  \:  \:  {\bigg(2 + 2\bigg) }^{2}  - 2

\rm \:  =  \:  \:  {\bigg(4\bigg) }^{2}  - 2

\rm \:  =  \:  \: 16 - 2

\rm \:  =  \:  \: 14

 \purple{ \boxed{\bf :\implies\: {x}^{2}  + \dfrac{1}{ {x}^{2}} = 14 }}

Now,

Consider,

 {\bf :\longmapsto\: {\bigg( {x}^{2} + \dfrac{1}{ {x}^{2} }  \bigg) }^{2}}

\rm \:  =  \:  \:  {(14)}^{2}

\rm \:  =  \:  \: 196

Hence,

  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \: \underbrace{ \boxed {\bf \: {\bigg( {x}^{2} + \dfrac{1}{ {x}^{2} }  \bigg) }^{2} = 196}}

More Identities to know:

  • (a + b)² = a² + 2ab + b²

  • (a - b)² = a² - 2ab + b²

  • a² - b² = (a + b)(a - b)

  • (a + b)² = (a - b)² + 4ab

  • (a - b)² = (a + b)² - 4ab

  • (a + b)² + (a - b)² = 2(a² + b²)

  • (a + b)³ = a³ + b³ + 3ab(a + b)

  • (a - b)³ = a³ - b³ - 3ab(a - b)
Similar questions